Peningkatan Kesadaran Generasi Muda Desa Mendana Raya Tentang Bahayanya Pernikahan Dini - Paniran Paniran; Made Sutha Yadnya; Bulkis Kanata; Kurnia Utami Rinjani Putri; Elya Kadariya (Jurnal Gema Ngabdi, 2023)
Mendana Raya Village is one of 16 villages in Keruak District, East Lombok Regency, West Nusa Tenggara Province. The obstacle that is often faced by Mendana Raya Village is the lack of knowledge about the age limit that is allowed to marry or the Marriage Age Maturity (PUP). So far, efforts have been made to make the Mendana Raya Village community aware of reducing the number of early marriages through lectures. An alternative method that researchers use to reduce the number of early marriages in Mendana Raya Village is to conduct counseling with the addition of several methods so that adults and children can understand them well. Some of the methods that the service uses are lectures, question and answer questions with prizes and discussions. The product of this counseling cannot be seen directly because it is knowledge, behavior and decisions between individuals. To find out the level of success of the counseling that was carried out, the servant conducted a short interview regarding Marriage Age Maturity to children and parents. The result after counseling is an increase in understanding and knowledge of each resident of Mendana Raya Village.